TRADISI PERKAWINAN MASYARAKAT BUGIS (STUDI KASUS TENTANG ”SARAPO”) DI DUSUN SUDIMAMPIR, DESA KARAMIAN KECAMATAN MASALEMBU KABUPATEN SUMENEP PROVINSI JAWA TIMUR - Muzakar, Ahmad; Mattiro, Syahlan; Azkia, Laila (Universitas Lambung Mangkurat, 2024)
One of the Bugis community's wedding traditions is sarapo which is located in Karamian Village, Masalembu District, Sumenep Regency. The study aims to (1) find out the meaning of sarapo (2) find out the applicable norms related to sarapo in the Bugis community in Sudimampir Hamlet, Karamian Village, Masalembu District, Sumenep Regency, East Java Province. The method used in this study is a qualitative method. The data source selected was purposive sampling and the informants in this study were 7 people, namely Mr. Amri, Mr. Hasbih, Mr. Abdurrahman, Mrs. Hawang, Mrs. Musdalifah, Mrs. Risnawati, and Mrs. Ruqiyah. The data collection techniques used were observation, interviews and documentation which were conducted on September 30, 2020. The data analysis techniques used in this study were data reduction, presentation, and drawing conclusions. The results of the study found that (1) there are 3 meanings of sarapo, namely: a) maintaining relationships in society, meaning that we cannot live without other people with this so that family or community relationships are maintained. b) respecting the guests, meaning that with the presence of the sarapo there is no longer any distinction in society. c) a symbol of marriage, in the sense that the community who sees the sarapo already knows that in the next few days there will be a wedding activity in the next few days. (2) There are 2 norms that apply to the sarapo, namely: a) slaughtering animals, meaning that before building the sarapo, the community must first slaughter animals with the intention that all these marriage activities, especially the sarapo, will run smoothly and without obstacles. b) it is forbidden to cross, if you violate it, your health will be disturbed, even bad luck and have an impact on the death of the child. Based on the results of this study, it is recommended that traditional leaders, religious leaders, community leaders, and the community must work together to provide appropriate advice and maintain the sustainability of this tradition. For the community who are the original owners of the tradition, this tradition must be maintained and not changed. It is hoped that the next generation can further improve and maintain this tradition and be the basis for being able to direct the social system in the future. To be a reference material for further research with problems related to marriage traditions in Bugis society in other areas